The Effect of Air Pollution on the Health of Urban Residents (Case Study in Jakarta) - Joko Sapto Pramono; Nuraini; Junardin Djamaluddin; Yoanita Hijriyati; Yusriati (Miracle Journal Get Press, 2025)
Air pollution is a major environmental issue affecting urban areas worldwide, with significant health implications for millions of residents. In Jakarta, rapid urbanization and industrial activities have contributed to deteriorating air quality, exposing the population to harmful pollutants such as particulate matter (PM₂.₅, PM₁₀), nitrogen dioxide (NO₂), sulfur dioxide (SO₂), ozone (O₃), and carbon monoxide (CO). This study aimed to analyze the impact of air pollution on public health in Jakarta, identify key hazardous pollutants, and evaluate the effectiveness of mitigation policies. A literature review approach and secondary data analysis were utilized, incorporating air quality monitoring data, epidemiological studies, and government reports. The results indicate that prolonged exposure to air pollutants correlates with increased cases of respiratory diseases (asthma, bronchitis, COPD), cardiovascular disorders, and overall mortality rates. The study also observes fluctuating air quality trends in Jakarta between 2020 and 2024, with periods of improvement attributed to regulatory interventions. Findings highlight the urgency of implementing stricter pollution control policies, promoting public transportation, and enhancing air quality monitoring systems. The study concludes that a multi-stakeholder approach, involving government, industry, and communities, is essential for sustainable urban air quality management. Future research should focus on the long-term effects of air pollution exposure and the effectiveness of policy measures in reducing health risks.